Disability and School Enrollment in Indonesia: A Comparative Analysis - Nur Hidayati; Dwini Handayani; Prita Nurmalia Kusumawardhani (South Sulawesi Education Development (SSED), 2026)
This study aims to analyze the relationship between disability and school participation opportunities and identify the source of school participation gaps between children with disabilities and non-disabilities. The data used came from the National Socio-Economic Survey (Susenas) in March 2021, with a Linear Probability Model analysis approach. The estimated results showed that children with disabilities had a lower chance of attending school by 13,57% compared to non-disabled children, meaning that there was a statistically significant difference. These findings indicate a marked gap in school participation between the two groups. Follow-up analysis using the Blinder-Oaxaca decomposition with non-disabilities as a reference group showed that about 15,34% of the gap in school participation could be explained by differences in observable characteristics. In contrast, most of the gaps, which were about 84,66%, came from differences in coefficients and unexplained factors. These results confirm that the unexplained component plays a dominant role in explaining the inequality of school participation between children with and without disabilities.